Coronavirus Disease 2019 (COVID-19) Re-infection by a Phylogenetically Distinct Severe Acute Respiratory Syndrome Coronavirus 2 Strain Confirmed by Whole Genome Sequencing. (25th August 2020) - To, Kelvin Kai-Wang; Hung, Ivan Fan-Ngai; Ip, Jonathan Daniel; Chu, Allen Wing-Ho; Chan, Wan-Mui; Tam, Anthony Raymond; Fong, Carol Ho-Yan; Yuan, Shuofeng; Tsoi, Hoi-Wah; Ng, Anthony Chin-Ki; Lee, Larry Lap-Yip; Wan, Polk; et al.
Abstract: Background: Waning immunity occurs in patients who have recovered from Coronavirus Disease 2019 (COVID-19). However, it remains unclear whether true re-infection occurs. Methods: Whole genome sequencing was performed directly on respiratory specimens collected during 2 episodes of COVID-19 in a patient. Comparative genome analysis was conducted to differentiate re-infection from persistent viral shedding. Laboratory results, including RT-PCR Ct values and serum Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) IgG, were analyzed. Results: The second episode of asymptomatic infection occurred 142 days after the first symptomatic episode in an apparently immunocompetent patient. During the second episode, there was evidence of acute infection including elevated C-reactive protein and SARS-CoV-2 IgG seroconversion. Viral genomes from first and second episodes belong to different clades/lineages. The virus genome from the first episode contained a a stop codon at position 64 of ORF8, leading to a truncation of 58 amino acids. Another 23 nucleotide and 13 amino acid differences located in 9 different proteins, including positions of B and T cell epitopes, were found between viruses from the first and second episodes. Compared to viral genomes in GISAID, the first virus genome was phylogenetically closely related to strains collected in March/April 2020, while the second virus genome was closely related to strains collected in July/August 2020. Conclusions: Epidemiological, clinical, serological, and genomic analyses confirmed that the patient had re-infection instead of persistent viral shedding from first infection. Our results suggest SARS-CoV-2 may continue to circulate among humans despite herd immunity due to natural infection. Further studies of patients with re-infection will shed light on protective immunological correlates for guiding vaccine design. Abstract : Our results suggest SARS-CoV-2 may continue to circulate among the human populations despite herd immunity due to natural infection or vaccination. Further studies of patients with re-infection will shed light on protective correlates important for vaccine design.